Antioxidant and Anticancer Effects of Red Okra (Abelmoschus esculentus L.) Ethanol Extract through In Vitro and In Vivo Colorectal Cancer Models - Wahyuningsih, Sri Puji Astuti; Mamuaya, Brigita Klara Krisdina; Dewi, Firli Rahmah Primula; Hapsari, Lukiteswari Dyah Tri; Kusuma, Baskara Wiku Adi; Nurhayati, Awik Puji Dyah (Pandawa Institute, 2026)
Colorectal cancer (CRC) remains the second leading cause of cancer-related mortality worldwide. Affordable herbal sources such as red okra (Abelmoschus esculentus L.) pods have gained attention as potential alternative therapies for CRC. This study aimed to evaluate the antioxidant and anticancer effects of red okra ethanol extract (ROE) using both in vitro and in vivo colorectal cancer models. The antioxidant activity of ROE was assessed using the DPPH assay, while cytotoxic activity was evaluated using the MTT assay on SW480 and HCT116 cell lines. An in vivo study was conducted using rats divided into six groups: normal control, negative control (MNU 10 mg/kg BW), positive control (MNU + methotrexate 0.08 mg/kg BW), and treatment groups receiving MNU combined with ROE at doses of 50, 100, and 200 mg/kg BW for 28 days. Serum levels of Bcl-2, COX-2, VEGF, and MMP-9 were analyzed, and histopathological evaluations of colon tissues were performed. Data were statistically analyzed using one-way ANOVA followed by Duncan’s post hoc test. Statistical significance was determined at p<0.05. ROE exhibited potent antioxidant activity (IC₅₀ = 59.66 ppm) and induced cytotoxic effects by reducing SW480 cell growth and inhibiting HCT116 cell proliferation. Moreover, ROE significantly decreased the expression of Bcl-2, COX-2, VEGF, and MMP-9. These biomarkers are associated with apoptosis inhibition, angiogenesis, inflammation, and metastasis, respectively. Histopathological analysis confirming reduced inflammatory infiltration and suppression of colon carcinogenesis. The optimal in vivo dose was 50 mg/kg BW. These findings support the development of ROE as a promising natural agent for colorectal cancer prevention and therapy.